STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI POLA KEMITRAAN KONSERVASI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG KABUPATEN MAROS - Fatmiah Fatmiah; Abdullah Abdullah; Nurliani Nurliani (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
This research aims to describe the socio-economic conditions of the community, assess the success of community empowerment programs, identify the driving and inhibiting factors of empowerment programs, and formulate community empowerment strategies for conservation partnership patterns in Bantimurung Bulusaraung National Park. This research was conducted at Bantimurung Bulusaraung National Park, District of Maros in July-August 2021. This research method uses a survey method. Data collection techniques using questionnaires and interviews. The data analysis used is descriptive statistics and SWOT analysis. The results of this study based on the results of the SWOT analysis that has been carried out identified 1) internal factors identified in empowerment there are seven strength factors & eight weakness factors. While the external factors there are nine factors of threats and opportunities. 2) The results of the analysis of internal factors have three strengths of empowerment with a score of 0.29, and there is one weakness with the lowest score of 0.15. Based on this analysis indicates that the internal factors are strong or very supportive of empowerment. 3) The results of the analysis of external factors show that opportunities and threats have one factor with a score of 0.23 and 0.08. 4) Based on a SWOT analysis of community empowerment strategies in Batimurung Bulusaraung National Park that can be done, namely helping productive economic businesses, building business networks by involving related parties, and optimizing the use of forest resources.